Decay rates for a coupled viscoelastic Lamé system with strong damping - Feng, Baowei; Li, Haiyan (Mathematical Modelling and Analysis, 2020)
In [6] Beniani, Taouaf and Benaissa studied a coupled viscoelastic Lamé system with strong dampings and established a general decay result. In this paper, we continue to study the system. Assuming gi0(t) ≤−ξi(t)Hi(gi(t)), i = 1,2, we establish an explicit and general decay result, which is optimal, to the system. This result improves earlier results in [6].